2021
DOI: 10.3390/cancers13051081
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Post-Translational Modification (PTM)—Disrupting Mutations in the Tumor Matrisome

Abstract: Background: To evaluate the occurrence of mutations affecting post-translational modification (PTM) sites in matrisome genes across different tumor types, in light of their genomic and functional contexts and in comparison with the rest of the genome. Methods: This study spans 9075 tumor samples and 32 tumor types from The Cancer Genome Atlas (TCGA) Pan-Cancer cohort and identifies 151,088 non-silent mutations in the coding regions of the matrisome, of which 1811 affecting known sites of hydroxylation, phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 89 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…The 3D and 2D structures of interaction between the proposed receptors and top-ranked drug molecules were constructed and visualized using USCF Chimera program and Discovery Studio Visualizer 2021 software ( Pettersen et al, 2004 ). Then, we validated the selected drug molecules with the cancer-related post-translational modification (PTM) sites (phosphorylation, ubiquitination, and succinylation) through docking analysis ( Hasan et al, 2016 ; Wang et al, 2020 ; Holstein et al, 2021 ; Mu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The 3D and 2D structures of interaction between the proposed receptors and top-ranked drug molecules were constructed and visualized using USCF Chimera program and Discovery Studio Visualizer 2021 software ( Pettersen et al, 2004 ). Then, we validated the selected drug molecules with the cancer-related post-translational modification (PTM) sites (phosphorylation, ubiquitination, and succinylation) through docking analysis ( Hasan et al, 2016 ; Wang et al, 2020 ; Holstein et al, 2021 ; Mu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been demonstrated that different types of PTM can be specifically distributed depending on protein functional category or its subcellular localization 24 , which indicates accumulation of type-specific PTMs in certain cancer phenotype and support a clue in tumorigenesis. Similarly, we observed a sensible variation of PTM types across cancer phenotypes in our study (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modification of cancer-associated extracellular matrix (ECM) alters the interaction of cancer cells with its microenvironment and influences malignancy and tumour growth [ 96 ]. Citrullination is produced through post-translational deamination of peptidyl-arginine and is catalysed by peptidylarginine deiminase (PAD).…”
Section: Post-translational Protein Modification In Colorectal Liver ...mentioning
confidence: 99%